Assessing the spatial variability of the 3 μm OH/H2O absorption feature in CM2 carbonaceous chondrites. (12th January 2023) - Schultz, Cody; Anzures, Brendan A.; Milliken, Ralph E.; Hiroi, Taki; Robertson, Kevin
Abstract: H2 O and OH are readily detected in hydrated minerals in CM chondrites via reflectance spectroscopy due to their characteristic vibration absorptions at infrared wavelengths. Previous spectroscopic work on bulk powdered CM chondrites has shown that spectral parameters, like the wavelength position of the "3 μm absorption feature, " vary systematically with the extent to which the samples have been aqueously altered. However, it is yet unclear how these spectral features may vary across an intact meteorite chip when measured at spatial scales smaller than that of the individual components of the meteorite. Here, we explore the spatial variability of this spectral feature and others on intact CM2 chips which, unlike powders, retain their petrologic and textural characteristics. We also model the modal mineralogy of the bulk meteorite powders and correlate this with key spectral features, demonstrating that microscope Fourier transform infrared spectroscopic mapping provides a powerful, rapid, and non‐destructive technique for assessing compositional diversity and variations in water–rock interactions in chondritic planetary materials. In all CM2 chondrites studied here, we find that variations in the position, shape, and strength of the 3 μm absorption feature reveal a single chondrite can exhibit as much spectral variation as the entire suite of CM2 chondrites. The observed variations in the position and shape of the 3 μm feature within individual CM2 chondrite chips suggest a range of alteration products (e.g., Mg‐rich to Fe‐rich phyllosilicates) are present and record sub‐mm scale variations in the amount and/or chemistry of the altering fluids. The samples having experienced the most progressive aqueous alteration show the least amount of variability in features like the 3 μm absorption band minimum position, whereas the least altered samples exhibit the most variability. We also find that the bulk spectral signatures in the least altered samples appear to be biased toward the spectral signatures of clasts versus matrix. By extension, asteroid reflectance spectra exhibiting 3 μm absorption features consistent with those measured here may be interpreted in a similar framework in which the spectrum of what may appear to be the least altered asteroids represents an average that belies the true diversity of mineralogy and chemistry of the body.